If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B(b + -7) = 0 Reorder the terms: B(-7 + b) = 0 (-7 * B + b * B) = 0 (-7B + bB) = 0 Solving -7B + bB = 0 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'B'. B(-7 + b) = 0Subproblem 1
Set the factor 'B' equal to zero and attempt to solve: Simplifying B = 0 Solving B = 0 Move all terms containing B to the left, all other terms to the right. Simplifying B = 0Subproblem 2
Set the factor '(-7 + b)' equal to zero and attempt to solve: Simplifying -7 + b = 0 Solving -7 + b = 0 Move all terms containing B to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + b = 0 + 7 Combine like terms: -7 + 7 = 0 0 + b = 0 + 7 b = 0 + 7 Combine like terms: 0 + 7 = 7 b = 7 Add '-1b' to each side of the equation. b + -1b = 7 + -1b Combine like terms: b + -1b = 0 0 = 7 + -1b Simplifying 0 = 7 + -1b The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
B = {0}
| x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x | | (1/2)(2x-10)=4 | | x^3-3x^2+9x-54=0 | | x^2-4=6 | | 8(y-5)=6-18 | | .20x+.25+9=.21 | | 4-15y=4 | | -14=(2/5)(9-2b) | | -32=(8/7)(3w-1) | | .80x+.25(60)=.70(x+60) | | c=0.90y+1.65 | | 28s-2=59s-64 | | 9=-9v^2+6v | | 4=(2/9)(4y-2) |